Rhein ameliorates inflammation, gut dysbiosis, and renal injury in obesity-related glomerulopathy mice - Xu, Minmin; Yu, Yue; Li, Lijie; Zhao, Kang; Lai, Jingjing; Wei, Lifang; Ge, Li (Frontiers in Pharmacology, 2025)
ObjectiveObesity-related glomerulopathy (ORG) lacks targeted therapies. Rhein, a bioactive anthraquinone from Rhei Radix et Rhizoma, was evaluated for its effects on inflammation, renal function, and gut microbiota in high-fat diet-induced ORG mice.MethodsC57BL/6J mice were fed a 60% fat diet for 12 weeks to establish ORG, followed by 300 mg/kg/day rhein free intake for 12 weeks. Serum cytokines (IL-6, TNF-α), renal histopathology, and 16S rRNA microbiome sequencing were analyzed.ResultsRhein significantly reduced body weight (P < 0.001), serum triglycerides (P < 0.01), and proteinuria (P < 0.001), while improving glomerular lesions. It also markedly lowered serum levels of IL-6, TNF-α, and creatinine. 16S rRNA sequencing revealed that rhein restored gut microbiota diversity (e.g., Chao1 index increased from 303.58 to 425.78) and reversed the Firmicutes/Bacteroidetes imbalance (76.86%–62.15%). Analysis of similarities (ANOSIM) further confirmed a significant difference in microbial community structure between the Rhein and Model groups (R = 0.926, p = 0.008).ConclusionRhein mitigates ORG progression is associated with anti-inflammatory, lipid-lowering, and microbiota-modulating mechanisms, offering a novel therapeutic strategy.